Upregulation of NR2A in Glutamatergic VTA Neurons Contributes to Chronic Visceral Pain in Male Mice - Meng-Ge Li; Shu-Ting Qu; Yang Yu; Zhenhua Xu; Fu-Chao Zhang; Yong-Chang Li; Rong Gao; Guang-Yin Xu (Neuroscience Bulletin, 2025)
Chronic visceral pain is a persistent and debilitating condition arising from dysfunction or sensitization of the visceral organs and their associated nervous pathways. Increasing evidence suggests that imbalances in central nervous system function play an essential role in the progression of visceral pain, but the exact mechanisms underlying the neural circuitry and molecular targets remain largely unexplored. In the present study, the ventral tegmental area (VTA) was shown to mediate visceral pain in mice. Visceral pain stimulation increased c-Fos expression and Ca 2+ activity of glutamatergic VTA neurons, and optogenetic modulation of glutamatergic VTA neurons altered visceral pain. In particular, the upregulation of NMDA receptor 2A (NR2A) subunits within the VTA resulted in visceral pain in mice. Administration of a selective NR2A inhibitor decreased the number of visceral pain-induced c-Fos positive neurons and attenuated visceral pain. Pharmacology combined with chemogenetics further demonstrated that glutamatergic VTA neurons regulated visceral pain behaviors based on NR2A. In summary, our findings demonstrated that the upregulation of NR2A in glutamatergic VTA neurons plays a critical role in visceral pain. These insights provide a foundation for further comprehension of the neural circuits and molecular targets involved in chronic visceral pain and may pave the way for targeted therapies in chronic visceral pain.